Electrical resistivity and induced polarization in the investigation of acid drainage in decommissioning a mine - Duz, Beatriz Guzzo [UNESP]; Moreira, César Augusto [UNESP]; Hartwig, Marcos Eduardo; Miano, Felipe Queiroz [UNESP]; Furlan, Lucas Moreira [UNESP] (FapUNIFESP (SciELO), 2025)
The opening and development of mines without previous planning can generate costly environmental liabilities that are difficult to recover. The Osamu Utsumi Mine was responsible for extracting uranium until 1995 in open pit mining operations. The sulfide rocks with residual ore are exposed and their interaction with groundwater and rainwater can generate acid drainage. This study aims to identify possible sources of acid drainage in the SE front of the pit using the geophysical methods, such as electrical resistivity and induced polarization. The analysis of the two-dimensional sections generated with the geophysical results allowed the recognition of low resistivity zones (<118 Ω.m) and high chargeability areas (>20 mV/V), interpreted as the presence of water and sulphide concentration, respectively. This combination of factors contributes to the generation of acid drainage. By determining the possible acid drainage generation points, the mine decommissioning process can become faster and more effective.
Keywords: acidic mine drainage; electrical resistivity; induced polarization; uranium